2016
DOI: 10.18632/oncotarget.8437
|View full text |Cite
|
Sign up to set email alerts
|

The GSK3β inhibitor BIS I reverts YAP-dependent EMT signature in PDAC cell lines by decreasing SMADs expression level

Abstract: The Yes-associated protein, YAP, is a transcriptional co-activator, mediating the Epithelial to Mesenchymal Transition program in pancreatic ductal adenocarcinoma (PDAC). With the aim to identify compounds that can specifically modulate YAP functionality in PDAC cell lines, we performed a small scale, drug-based screening experiment using YAP cell localization as the read-out. We identified erlotinib as an inducer of YAP cytoplasmic localization, an inhibitor of the TEA luciferase reporter system and the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Zhao et al [ 17 ] found that ING5 significantly inhibited the phosphorylation of PI3K and Akt in breast cancer cells, leading to MET. In addition, EMT is positively associated with aberrant activation of Wnt or the PI3K/Akt pathway, which activates GSK-3β and stabilizes β-catenin [ 20 , 21 ]. We found that PI3K, Akt, and β-catenin were decreased in ING5 transfectants of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [ 17 ] found that ING5 significantly inhibited the phosphorylation of PI3K and Akt in breast cancer cells, leading to MET. In addition, EMT is positively associated with aberrant activation of Wnt or the PI3K/Akt pathway, which activates GSK-3β and stabilizes β-catenin [ 20 , 21 ]. We found that PI3K, Akt, and β-catenin were decreased in ING5 transfectants of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Yes-associated protein (YAP) is a transcriptional factor of the Hippo signaling pathway ( 11 ). A number of studies have supported a critical role for YAP in different types of cancer, including breast and lung cancer and pancreatic ductal adenocarcinoma (PDAC) ( 12 , 13 ). YAP has been demonstrated to be an essential promoter of the mutant KRAS oncogenic program, specifically inducing the expression of secreted factors such as CTGF and CYR61, and interacting with FOS, a proto-oncogene, to regulate the expression of EMT-associated genes such as E-cadherin, SLUG, SNAIL and Vimentin ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of the evaluated treatments in pancreatic cancer to date, only verteporfin (33,34) has a direct effect upon Hippo signaling. Erlotinib (35), BIS 1 (35) and LY3009120 (33) indirectly affect YAP and TAZ signaling. The mechanism of action is not fully clarified for several natural substances, such as curcumin (36), resveratrol (37), Stiehopus japonieus acidic mucopolysaccharide (38) and pseudolaric acid B (39).…”
Section: Therapeutic Targeting Of Hippo Signalingmentioning
confidence: 99%